MUNASAKHAT; METODE PRAKTIS DALAM PEMBAGIAN HARTA WARIS - Ainun Barakah (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2015)
This study aims to find practical methods in the division of inheritance in a situation where one heir dies before the inheritance of first mayyit allocated, with one practical step, without counting the manual portion of each heir of first mayyit and second mayyit. This munasakhat method has several supporting theories discussed to help solving the cases easily, those are four nasab (النسب الأربعة) theory and inkisar.